AI training for automated data extraction from clinical records (2021)
Most hospitals and government offices in Colombia have no centralized systems to efficiently collect data for evidence generation for academic purposes and policymaking. In addition, physicians in small-to-middle-size cities do not participate in conducting clinical research due to significant gaps in resources and personnel skilled in data science. It results in a lack of information about the prevalence and impact of diseases, limiting municipalities' power to decide when developing prevention, screeningdiagnosis, and treatment programs. microscopIA, through the current approach, has grown a platform to allow physicians to collect data matching a research project while collecting massive data for AI training and policymaking